2002
DOI: 10.1128/aem.68.1.346-355.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Novel Red Green Nonsulfur Bacteria from Five Distinct Hot Spring Communities in Yellowstone National Park

Abstract: We characterized and compared five geographically isolated hot springs with distinct red-layer communities in Yellowstone National Park. Individual red-layer communities were observed to thrive in temperatures ranging from 35 to 60°C and at pH 7 to 9. All communities were dominated by red filamentous bacteria and contained bacteriochlorophyll a (Bchl a), suggesting that they represented novel green nonsulfur (GNS) bacteria. The in vivo absorption spectra of individual sites were different, with two sites showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 23 publications
5
53
0
Order By: Relevance
“…Nübel et al (35) suggested the possibility of temperature-adapted strains of Roseiflexus spp. based on differences in phylogeny and temperature distribution of SSU rRNA sequences cloned from hot spring mats (6,16). Differences in light absorption between strains RS1 and RS2 may also reflect differential adaptation that might help explain the cooccurrence of many Roseiflexus-like SSU rRNA sequences at a single mat location.…”
Section: Discussionmentioning
confidence: 99%
“…Nübel et al (35) suggested the possibility of temperature-adapted strains of Roseiflexus spp. based on differences in phylogeny and temperature distribution of SSU rRNA sequences cloned from hot spring mats (6,16). Differences in light absorption between strains RS1 and RS2 may also reflect differential adaptation that might help explain the cooccurrence of many Roseiflexus-like SSU rRNA sequences at a single mat location.…”
Section: Discussionmentioning
confidence: 99%
“…Such bacteria could thrive in sulfide-rich environments similar to those preferred by green sulfur bacteria except that they would possibly require a much higher light intensity to sustain reasonable growth rates. Interestingly, such bacteria that are phylogenetically related to the green filamentous bacteria have already been identified and isolated (4,17,29). Heliothrix oregonensis (29) and Roseiflexus castenholzii (17) are photoheterotrophs isolated from hot springs in Oregon and Japan, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1), and assumed that these were filamentous phototrophs since they were recovered from Bchl-rich mat layers (7). Interestingly, they observed some site-specific phylogenetic clustering and did not detect any type C-like organisms in their samples (7). It will be interesting to unravel the environmental conditions that govern the differential compositions of these microbial mats, which are still little understood.…”
Section: Vol 68 2002 Properties Of Uncultivated Chloroflexaceae 4599mentioning
confidence: 99%
“…Recently, related 16S rRNA gene sequences from low-temperature Yellowstone hot springs and small geyser splash zones containing thick mats exhibiting distinct red layers (clusters YRL-A and YRL-B in Fig. 1) have been reported (7).…”
mentioning
confidence: 96%